2012
DOI: 10.1007/s00464-012-2172-0
|View full text |Cite
|
Sign up to set email alerts
|

Thoracoscopic esophagectomy in the prone position

Abstract: The ideal approach within minimally invasive esophageal surgery continues to be a subject of debate since no single method has produced outstanding results. Further clinical studies are required to see whether ergonomic advantages of the prone position can be translated into improved patient outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(18 citation statements)
references
References 83 publications
0
18
0
Order By: Relevance
“…24,54,55 LMAs can be used to maintain the airway if the endotracheal tube becomes dislodged as it can be rapidly inserted without layngoscopy. 24,54 However, it should be taken into consideration that prone as well as lateral position causes dilation in the airway due to gravitational effects of local anatomic structures.…”
Section: Endotracheal Tube and Lma Displacementmentioning
confidence: 99%
“…24,54,55 LMAs can be used to maintain the airway if the endotracheal tube becomes dislodged as it can be rapidly inserted without layngoscopy. 24,54 However, it should be taken into consideration that prone as well as lateral position causes dilation in the airway due to gravitational effects of local anatomic structures.…”
Section: Endotracheal Tube and Lma Displacementmentioning
confidence: 99%
“…However, there has been no definitive consensus as to whether this procedure should be performed with the patient in the lateral decubitus or prone position [11] adding to the observed wide variability in the performance of MIE [12]. A systematic review of the literature between 1994 and 2010 showed no convincing evidence that prone position is superior to lateral decubitus although most authors comment that the prone position is associated with superior surgical ergonomics and theoretically offers a number of physiological benefits [11].…”
Section: Introductionmentioning
confidence: 97%
“…[2,13] The technique could also better reveal the left RLN; [14] nevertheless, its largest drawback is that during emergency cases, which require position changes and thoracotomy, difficulties arise. [15] Therefore, the prone position is unsuitable for situations closely associated with the blood vessels and trachea membrane and in esophageal cancer patients who received neo-adjuvant chemotherapy. [16,17] After the performance of an artificial pneumothorax in the semi-prone position, microinvasive esophageal cancer resection may have some advantages.…”
Section: Discussionmentioning
confidence: 99%